Commercial manufacturing of current good manufacturing practice peptides spanning the gamut from neoantigen to commercial large-scale products - Michael W. Pennington; Brant Zell; Chris J. Bai (Elsevier, 2021)
Peptide therapeutics represents a significant and growing area for manufacturing companies utilizing both chemical and recombinant methods. Approvals for orally administered peptides such as Linzess® (linaclotide), Trulance® (plecanatide), and most recently Rybelsus® (semaglutide) are pushing manufacturing requirements to quantities routinely exceeding 100 kg and potentially metric ton quantities especially for conditions such as type II diabetes where a worldwide epidemic creates the need for truly huge quantities. Additionally, personalized medicine has created a need for rapid synthesis of multiple peptides manufactured and released under current good manufacturing practices standards in the 50 mg range with a speedy delivery (<4 weeks). These two aspects of peptide manufacturing represent the gamut, which companies must span in order to meet all of their potential customer requirements. The purpose of this review is to cover some of the newer aspects in manufacturing required to meet the demand that these two extremes represent.